2012
DOI: 10.1681/asn.2011070645
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Signaling Promotes TGFβ-Dependent Renal Fibrosis

Abstract: The mechanisms by which angiotensin II (Ang II) promotes renal fibrosis remain incompletely understood. Ang II both stimulates TGFb signaling and activates the EGF receptor (EGFR), but the relative contribution of these pathways to renal fibrogenesis is unknown. Using a murine model with EGFRdeficient proximal tubules, we demonstrate that upstream activation of EGFR-dependent ERK signaling is critical for mediating sustained TGFb expression in renal fibrosis. Persistent activation of the Ang II receptor stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
248
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(266 citation statements)
references
References 38 publications
(47 reference statements)
17
248
1
Order By: Relevance
“…Boosting survival and regeneration of TECs might be renoprotective and antifibrotic as, for example, suggested for CSF-1 (143). Other TECs factors driving fibrosis include Notch (144), lipocalin-2 (NGAL) (28), kidney injury molecule-1 (KIM-1) (145), b-catenin signaling (146), and the EGFR (147,148). Paracrine signaling from damaged TECs is probably one of a major mechanisms driving renal fibrosis ( Figure 3).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 98%
“…Boosting survival and regeneration of TECs might be renoprotective and antifibrotic as, for example, suggested for CSF-1 (143). Other TECs factors driving fibrosis include Notch (144), lipocalin-2 (NGAL) (28), kidney injury molecule-1 (KIM-1) (145), b-catenin signaling (146), and the EGFR (147,148). Paracrine signaling from damaged TECs is probably one of a major mechanisms driving renal fibrosis ( Figure 3).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 98%
“…1 Our recent studies demonstrated that NADPH oxidase-derived ROS production-mediated c-Src kinase activation was an upstream mediator of EGFR activation in renal proximal tubular epithelial cells in response to chronic angiotensin II treatment. 15 A recent study also indicated that inhibition of c-Src kinase prevented progression of diabetic nephropathy. 27 To examine whether NADPH oxidase-dependent ROS production induced c-Src kinase-dependent activation of the EGFR-ERK signaling pathway and TGF-b-Smad2/3 signaling pathway in podocytes, WT diabetic mice were administered a mitochondria-targeted ROS scavenger, mito-tempol (10 mg/kg per day intraperitoneally), or a cell-permeable NADPHoxidase inhibitor, apocynin (5mg/kg per day intraperitoneally), for 3 weeks with the first dose being given 2 days after initiation of diabetes.…”
Section: Ros-mediated Podocyte C-src and Egfr/erk Phosphorylationmentioning
confidence: 99%
“…26 Our previous study found that in response to chronic angiotensin II infusion in renal proximal tubule epithelial cells, TGF-b-Smad2/3 signaling pathway was activated through a c-Src kinasemediated EGFR-ERK signaling pathway activation. 15 To determine whether the TGF-b signaling pathway was activated in diabetic podocytes through an EGFR-dependent mechanism, we examined and found increased phosphorylation levels of EGFR at three different sites (Y845, Y1068 and Y1173) as well as increased phosphorylation of c-Src, ERK1/2 as well as Smad2/3. The expression levels of TGF-b and fibronectin were upregulated in the glomeruli isolated from WT diabetic mice.…”
Section: Podocyte Egfr Deletion Attenuated Albuminuria and Podocyte Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…2). These sites are directly involved in activating the RAS, MAPK, PI3K, and c-Src pathways (27,47,48) and indirectly lead to activation of WNT, NF-B, and TGF-␤ signaling via these former pathways. Hence, these particular phosphorylation sites were examined as they activate pathways previously found to be inhibited by NDRG1 in these cells (4,6,8,(17)(18)(19).…”
Section: Panel II and C Panel Ii)mentioning
confidence: 99%